Effect of particle size and surface area of corn on pig performance and nutrient digestibility - Jih-Fang Wu; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1984)
Two feeding trials and two digestion trials were conducted to evaluate the effects of particle size and surface area of corn on the performance and nutrient digestibility of weaning and finishing pigs. The effects of particle size on production rate and grinding efficiency also were evaluated. Production rate and grinding efficiency decreased as particle size decreased. Average daily gain was not influenced by particle size. Feed intake tended to decrease as particle size decreased with the lowest feed intake on the fine partice size diet. Feed efficiency tended to improve as particle size decreased. The incidence of ulceration in the esophageal region of the stomach of finishing pigs increased as particle size of diet decreased. Digestibility of dry matter, nitrogen and energy improved as particle size decreased or surface area increased with diets for both weaning and finishing pigs.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Particle size; Surface area; Corn; Nutrient digestibility; Performance